Knowledge of Pregnant Women about Pregnancy Gingivitis and Children Oral Health - Togoo, Rafi A.; Al-Almai, Balsam; Al-Hamdi, Fatimah; Huaylah, Salha H.; Althobati, Mashael; Alqarni, Safeyah (European Journal of Dentistry, 2019)
Objective A cross-sectional questionnaire-based study was carried out among 251 pregnant women to assess their level of knowledge and perception regarding pregnancy gingivitis and the oral health of new born children.Materials and Methods A self-administered validated questionnaire was distributed among pregnant women visiting the Child and Maternity Hospital, Ministry of Health, Aseer, Saudi Arabia. The questionnaire included the questions related to their knowledge/awareness about cause, treatment, preventive measures, and the adverse effects of gingivitis on oral health of a woman.Statistical Analysis The data was entered into Microsoft excel sheet and put to statistical analysis using SPSS (version 17). Descriptive analysis and also chi-squared test was used for comparison.Results Majority of pregnant women were found unaware about developing of pregnancy gingivitis as well as the cause, effects, treatment, and preventive measures for the same. Most of the subjects agreed that it was essentially required to have oral health education before their pregnancy term would start.Conclusion Most of the pregnant women said that they were unaware about pregnancy gingivitis, though few reported of being aware about it. It is inferred that the collaborative efforts between general dentists, pediatric dentists, public health dentists, and medical professionals are needed to raise awareness among pregnant women regarding timely dental care to avoid the adverse pregnancy related outcomes due to gingivitis and periodontitis.
Keywords: pregnancy; gingivitis; knowledge; women